A resilience assessment framework for slopes considering multiple performance indicators - Shiyuan Ju; Jinqing Jia; Yong Zhao; Xin Xiang; Bingxiong Tu (Scientific Reports)
Abstract The performance assessment of slopes during various disturbances is important to ensure the safe service of slopes. Due to the four characteristics of slope engineering, it is difficult for existing resilience evaluation models to accurately reflect slope performance. To address this problem, a resilience evaluation model applicable to slopes was developed in this study. In this model, a typical slope performance curve is proposed according to the characteristics of slope engineering and the calculation formula of slope resilience metric is derived. In order to facilitate engineering application, this study proposes a slope resilience assessment framework with the evaluation model as the core. In the resilience assessment framework, a multi-indicator system for slope performance was established to cover the slope components, and the CRITIC theory was used to combine the subjective and objective weights for each indicator. Finally, the proposed slope resilience assessment framework was applied to a slope case under the influence of continuous excavation and rainfall. The results show that the proposed resilience assessment framework can more accurately reflect the performance variations of slopes during disturbance and recovery processes than the existing model, and the resilience metric is 23.4% higher than that of the existing model. This study was the first attempt to establish a resilience assessment framework applicable to slopes, which informs subsequent research.